Answer:
-3 and 6
Step-by-step explanation:
-3 + 6 = 3
-3 * 6 = -18
Answer:
f^-1(x) = (x -2)/3
Step-by-step explanation:
To find the inverse function, swap x and y, then solve for y.
y = 3x +2 . . . . given function
x = 3y +2 . . . . inverse relation
x -2 = 3y . . . . subtract 2
(x -2)/3 = y . . . divide by 3
f^-1(x) = (x -2)/3 . . . . in functional form
Parallel lines have the same slope, so the slope of the other line is also 1/6
Answer: T= 3.54
Step-by-step explanation:
Step 1
Given that
The time period, T, s doirectly proportional to the square root of the length, d, of the pendulum, we have that
T ∝
Introducing the constant of proportionality, we have that
T= K.
Step 2
When d=6, T=5, K =?
T= K.
5 = k
5= k x 2.44949
k =5/2.44949
k =2.041
Therefore, when d = 3 , T= ?
T= K
T= 2.041 x
T= 3.53511≈ 3.54
A. the data is decreasing so sales are bad.
b.